2010
DOI: 10.3109/13561820903550796
|View full text |Cite
|
Sign up to set email alerts
|

Changing stress while stressing change: The role of interprofessional education in mediating stress in the introduction of a transformative technology

Abstract: The introduction of a transformative technology into practice settings can affect the functioning of interprofessional teams, placing stress on interprofessional relationships, thus slowing adoption and change. This study explored the potential of an interprofessional education (IPE) approach to mediate this stress and facilitate the adoption of a transformative technology- Image Guided Radiation Therapy (IGRT). Oncologists, physicists, and therapists in radiation medicine who attended an interprofessional IGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…The field of radiation oncology is expected to continue to evolve [17] and postgraduate training programs for RO, MP and RTT must adapt to keep pace with clinical practice [1]. In addition to evolving clinical content the practice of medicine is changing with greater emphasis on interprofessional teams [2, 18]. In CanMEDS 2015, the updated competency framework for physicians, the competencies of ‘effective teams’, ‘interprofessional heath care’ and patient quality and safety are explicitly defined as key concepts [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The field of radiation oncology is expected to continue to evolve [17] and postgraduate training programs for RO, MP and RTT must adapt to keep pace with clinical practice [1]. In addition to evolving clinical content the practice of medicine is changing with greater emphasis on interprofessional teams [2, 18]. In CanMEDS 2015, the updated competency framework for physicians, the competencies of ‘effective teams’, ‘interprofessional heath care’ and patient quality and safety are explicitly defined as key concepts [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to improving skills acquisition, simulation offers an opportunity to teach and assess competencies such as teamwork, and interprofessional collaboration. However, there are challenges with interprofessional team training including addressing interprofessional content depth versus interprofessional learning objectives [2] and professional territoriality. Our study has demonstrated that radiation medicine trainees from RO, MP and RTT have limited clinical exposure to each other in traditional educational models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 For example, highly experienced therapists are often challenged to master new technologies, learning alongside (and sometimes quite differently from) younger generations of therapists. They become novices in some senses, even as they teach students who are interacting with patients for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…3,7,8 A number of studies have recognised the need to ensure radiation therapists possess the knowledge and skills necessary to manage new clinical information presented during the course of treatment delivery. 7,11,13 More recently, however, there has been increased focus on the evolving uses of CBCT images made possible through harnessing this additional soft-tissue information, such as adaptive planning, without considering the consequences for radiation therapists or the interprofessional team in which they work. Some have also discussed a shift in responsibility for assessment of positioning accuracy and approaches to achieve this.…”
Section: Introductionmentioning
confidence: 99%